Variability and Costs of Low Value Preoperative Testing for Carpal Tunnel Release Surgery - Harris, Alex HS (Anesth Analg, 2019)
BACKGROUND: The American Society of Anesthesiologists’ (ASA) Choosing Wisely Top-5 list of activities to avoid includes: “Don’t obtain baseline laboratory studies in patients without significant systemic disease (ASA I or II) undergoing low-risk surgery - specifically complete blood count, basic or comprehensive metabolic panel, coagulation studies when blood loss (or fluid shifts) is/are expected to be minimal.” Accordingly, we define low value preoperative tests (LVTs) as those performed prior to minor surgery in patients without significant systemic disease. The objective of the current study was to examine the extent, variability, drivers, and costs of LVTs prior to carpal tunnel release (CTR) surgeries in the US Veterans Health Administration (VHA). METHODS: Using Fiscal Year (FY) 2015–17 data derived from the VHA Corporate Data Warehouse, we determined the overall national and facility-level rates and associated costs of receiving any of eight common LVTs in the 30 days prior to CTR in ASA Physical Status (ASA-PS) I-II patients. We also examined the patient, procedure, and facility factors associated with receiving at least one LVT with mixed-effects logistic regression, and the number of tests received with mixed-effects negative binomial regression. RESULTS: From FY15–17, 10,000 ASA Class I-II patients received a CTR by 699 surgeons in 125 VHA facilities. Overall, 47.0% of patients had a CTR that was preceded by at least one LVT, with substantial variability between facilities (range = 0–100%; Interquartile Range = 36.3%), representing $339,717 in costs. Older age and female gender were associated with higher odds of receiving at least one LVT. Local vs. other modes of anesthesia was associated with lower odds of receiving at least one LVT. Several facilities experienced large (>25%) increases or decreases from FY15 to FY17 in the proportion of patients receiving at least one LVT. CONCLUSIONS: Counter to guidance from the ASA, we found that almost half of CTRs performed on ASA Class I-II VHA patients were preceded by at least one LVT. Although the total cost of these tests is relatively modest, CTR is just one of many low-risk procedures (e.g., trigger finger release, cataract surgery) that may involve similar preoperative testing practices. These results will inform site selection for qualitative investigation of the drivers of low value testing, and the development of interventions to improve preoperative testing practice, especially in locations where rates of LVT are high.